What Does Social Justice Look Like When Sitting With Clients? A Qualitative Study of Teaching Clinical Social Work From a Social Justice Perspective. (2nd July 2020) - Asakura, Kenta; Strumm, Brianna; Todd, Sarah; Varghese, Rani
ABSTRACT: The profession of social work emphasizes social justice in its service delivery, yet there is a paucity of literature on how to teach clinical practice from a social justice perspective. This qualitative study with Canadian social work educators ( n =12) suggests the following ways in which educators taught clinical social work from a social justice perspective: (1) integrating critical social theories in conceptualizing clinical practice, (2) engaging in transformative pedagogies, and (3) navigating professional commitments. While addressing various forms of social injustices is a mandate for all social workers, enactment of social justice within clinical practice remains an area of concern. Results suggest concrete ways in which social work educators can engage students in developing their commitment to social justice.